FROM ANXIETY TO HARSH WORDS: A STUDY OF ACADEMIC ANXIETY AND VERBAL AGGRESSIONS ON SOCIAL MEDIA AMONG STUDENST - Naurah Kinantan Abdillah; Belva Nur Nabila; Azeimul Kubro; Zahra Agusticia; Wiwik Juwarini Prihastiwi (P3I UMSurabaya, 2025)
This study aims to determine the relationship between academic anxiety and verbal aggression on social media among university students. The method used was a quantitative approach with a correlational design. There were100 randomly selected students as respondents. The instruments used in this study were two psychological scales, namely the academic anxiety scale and the verbal aggression scale on social media, each consisting of 10 itemsusing a 4-point Likert scale. The results of Pearson's correlation analysis showed a coefficient value of r = 0.324with a significance of p =0.001 (p < 0.05), which means that there is a positive and significant relationship between academic anxiety and verbal aggression on social media. These findings indicate that the higher the level of academic anxiety, the greater the tendency for students to exhibit verbally aggressive behavior on social media. The percentage of verbalaggression was very low at 9%, low at 18%, moderate at 48%, high at 16%, and very high at 9%.